2017
DOI: 10.3145/thinkepi.2017.05
|View full text |Cite
|
Sign up to set email alerts
|

Information Schools: estado actual, tendencias y propuestas

Abstract: López-Borrull, Alexandre; Cobarsí-Morales, Josep (2017). Information Schools: estado actual, tendencias y propuestas". Anuario ThinkEPI, v. 11, pp. 53-57. https://doi.org/10.3145/thinkepi.2017.05 Resumen: Se presenta una panorámica sobre las iSchools y su evolución en los últimos años. Se describe el crecimiento en todo el mundo y sus perspectivas de futuro. Por primera vez las universidades adheridas a iSchools de fuera de los Estados Unidos son más numerosas que las estadounidenses. Asimismo, se están c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The analysis by Rafiq et al (2017) revealed that training offered in LIS Schools are not fulfilling the requirements of LIS professionals. Some studies (López-Borrull and Cobarsí-Morales, 2017;de Alwis Jayasuriya et al, 2021;Muzamil and Nabeel, 2021) indicate that there is a lack of suitable training programmes and that LIS professionals are equipped with traditional knowledge for specialised librarianship roles, but the skills required in the new academic context and job market are given little importance in the existing LIS curriculums. Considering the ever-evolving ICT environment, LIS professionals need to develop high skills to adapt to these changes; thus, Ameen (2009) suggests that LIS schools should come forward to play their role in training working librarians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis by Rafiq et al (2017) revealed that training offered in LIS Schools are not fulfilling the requirements of LIS professionals. Some studies (López-Borrull and Cobarsí-Morales, 2017;de Alwis Jayasuriya et al, 2021;Muzamil and Nabeel, 2021) indicate that there is a lack of suitable training programmes and that LIS professionals are equipped with traditional knowledge for specialised librarianship roles, but the skills required in the new academic context and job market are given little importance in the existing LIS curriculums. Considering the ever-evolving ICT environment, LIS professionals need to develop high skills to adapt to these changes; thus, Ameen (2009) suggests that LIS schools should come forward to play their role in training working librarians.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, most of the LIS schools have already integrated digital librarianship in their taught programmes, and recently, there has been an increase in data literacy, as data is a core field of action for the European chapter of iSchools and one of the priorities of the European Commission and its European Data Portal (Audunson and Shuva, 2016;López-Borrull and Cobarsí-Morales, 2017;Wang, 2018;Van Hesteren and van Knippenberg, 2021). However, there is still a gap in education about openness (Rodriguez, 2015), which has not yet been fully embraced by LIS schools or programmes (Chiware, 2020).…”
Section: Type Number Of Libraries Detailmentioning
confidence: 99%
See 1 more Smart Citation